2021
DOI: 10.1002/dad2.12228
|View full text |Cite
|
Sign up to set email alerts
|

Association of walking energetics with amyloid beta status: Findings from the Baltimore Longitudinal Study of Aging

Abstract: Introduction:Higher energetic costs for mobility predict gait speed decline. Slow gait is linked to cognitive decline and Alzheimer's disease (AD). Whether the energetic cost of walking is linked to AD pathology is unknown. We investigated the cross-sectional association between the energetic cost of walking, gait speed, and amyloid beta (Aβ) status (+/−) in older adults.Methods: One hundred forty-nine cognitively normal adults (56% women, mean age 77.5 ± 8.4 years) completed customary-paced walking assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…In the present study we found that adults with lower slow‐paced walking V̇O 2 (i.e., more efficient energy use) had less WMHs. This finding complements our recent research that found a lower energetic cost of walking was associated with less Aβ deposition, a defining pathophysiologic feature of AD, and an attenuated rate of brain atrophy within regions that are vulnerable to age‐ and AD‐related neurodegeneration 27,28 . This study also observed that peak‐paced walking V̇O 2 , an estimate of aerobic capacity, was negatively associated with WMHs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study we found that adults with lower slow‐paced walking V̇O 2 (i.e., more efficient energy use) had less WMHs. This finding complements our recent research that found a lower energetic cost of walking was associated with less Aβ deposition, a defining pathophysiologic feature of AD, and an attenuated rate of brain atrophy within regions that are vulnerable to age‐ and AD‐related neurodegeneration 27,28 . This study also observed that peak‐paced walking V̇O 2 , an estimate of aerobic capacity, was negatively associated with WMHs.…”
Section: Discussionsupporting
confidence: 88%
“…[24][25][26] More recent evidence suggests these measures of walking energetics are also associated with AD-related pathology (amyloid beta [Aβ] deposition), white and gray matter brain volume, and cognitive performance in cognitively unimpaired midto late-aged adults. [27][28][29][30][31][32] Collectively, these findings suggest that the energy costs for mobility may reflect underlying changes that precede adverse changes in cognitive and motor function. Moreover, given that cerebral vascular dysfunction likely contributes to age-and disease-related pathology (e.g., brain atrophy, Aβ), it may underlie the previously observed walking energetics-brain associations.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The current study adds to this body of literature by illustrating that energetic cost of walking can be informative beyond measures of fitness, showing stronger associations with future brain changes, and adding to the growing body of literature linking the brain and aspects of mobility. Indeed, another recent study from the BLSA further showed that energetic cost of usual-paced walking was associated with accelerated annual increase in ventricular volume and decline in hippocampal volume 28 . Future research is needed to fully understand the association between the energy needed for walking at various speeds and brain volumes, especially among those less healthy than BLSA participants who may be more susceptible to dementia-related pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders caused by neurological disorders increase energy expenditure during walking ( 16 , 20 , 21 ), making patients more prone to fatigue when walking ( 16 , 22 ). Patients with stroke ( 22 ), PD ( 16 ), Alzheimer's disease (AD) ( 23 ), MS ( 24 ), and spinal cord injury (SCI) ( 25 ) exhibit higher oxygen consumption compared with healthy individuals. The mechanisms underlying the high energy cost in patients with CNCs may include tremors ( 16 ), walking biomechanics ( 26 ), and neural mechanisms ( 27 ).…”
Section: Introductionmentioning
confidence: 99%